Influence of CO2 presence on propane conversion routes over Cr- and Ga-doped PtCe/Al2O3 catalysts - Ballesteros-Plata, Daniel; Barroso-Martín, Isabel; Cecilia-Buenestado, Juan Antonio; Concepción, P.; López Nieto, José Manuel; Rodríguez-Castellón, Enrique; Infantes-Molina, Antonia (Elsevier, 2025)
A set of catalysts containing Cr- or Ga-doped Pt-CeO2 supported on alumina (PCA, Cr-PCA and Ga-PCA) were synthesized by incipient wetness impregnation and tested in propane conversion processes. The catalysts were studied in the propane conversion process with or without CO2 in the feed. In all cases, an enhancement in stability was found when CO2 was present in the reaction medium despite the lower catalytic activity. As well, all catalysts presented a higher propylene selectivity in the absence of CO2, indicating that the direct dehydrogenation of propane is the main reaction route. Moreover, CO2-assisted propane cracking to ethylene is favoured over propane reforming or direct cracking, given the minimal selectivity to other products like methane. With regards to the catalyst composition, Cr-PCA catalyst was the most active catalyst both in the absence and presence of CO2, due to the presence of weak acidity and coexistence of Cr3 + and Cr6+ redox species, as evidenced by XPS analysis. Ga-PCA catalyst was more selective to propylene, indicating that higher acidity of weak-to-medium nature along with formation of low coordinated Ga3+ species is beneficial for the CO2-ODH process. Raman, DTG and XPS analyses after reaction with CO2 showed that the deactivation of the catalysts was mainly due to carbon deposits of amorphous and graphitic nature on the surface of the catalysts.
Keywords: Propano; Catálisis; Cromo; Galio; Propane; Catalysis; CO2-ODHP; Noble metal; Ceria; Chromium; Gallium